ASAS ULTIMUM IN REMEDIUM DALAM TINDAK PIDANA KEIMIGRASIAN - Rizki Putra (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
In order to support the Government's Nawacita program and carry out the functions of facilitators of community welfare development, the Directorate General of Immigration provides several immigration facilities that aim to attract foreign tourists and foreign investors to enter and invest their capital in Indonesia including BVK and Visa on Arrival (VOA). However, this policy is often misused by foreigners who enter and are in the territory of Indonesia to carry out activities that are contrary to the provisions of laws and regulations, therefore there is a need to impose sanctions on foreigners who violate statutory provisions. In the application of criminal law, it is known as the principle of